Kemampuan Pelafalan Bunyi Vokal Dalam Bahasa Jerman - Nurul Arini Julyarti; Nurming Saleh; Syamsu Rijal (Universitas Negeri Makassar, 2021)
Abstract. This research is descriptive quantitative. This research aims to obtain data andinformation about the ability of students in the pronunciation of long and shor vowel sounds in german by students X IPA 4 SMAN 14 Gowa. As well, to obtain about the factors supporting and inhibitig that influence pronunciation of German vowel sounds. The data of this research was obtained through a pronunciation test and questionnaire. The population of this research by students X IPA 4 class at SMAN 14 Gowa with the total of 36 students. The sampel of this research is 20 students obtained using random technique. The result of the pronunciatin test showed an average score of 64.4 and were in the enaugh category. The data analysis to obtain in the results, namely the abilty to pronunciation vowel sounds in German by students X IPA 4 SMAN 14 Gowa is 64.4 or enaugh category. From the results of the distribution of the questionnaire data obtained that there are two factors that play an important role in influencing students' listening skills, namely: 1) Supporting factors, the teacher corrects the sudent’s pronounciation of vowel sound. 2) The inhibiting factor, students think that German is difficult.